FORMULATION AND EVALUATION OF MATRIX TYPE TRANSDERMAL PATCHES OF GLIBENCLAMIDE (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Matrix type transdermal patches containing Glibenclamide were prepared using three different polymers by solvent evaporation technique. Aluminium foil cup method was used as a substrate. Polyethylene glycol (PEG) 400 was used as plasticizer and Dimethyl sulfoxide (DMSO) was used as penetration enhancer. The physicochemical parameters like weight variation, thickness, folding endurance, drug content, % moisture absorption and % moisture loss were evaluated. In vitro drug release studies and skin permeation studies were carried out using Franz diffusion cell. Cumulative amount of drug released in 12 hours from the six formulations were 55.467, 52.633, 47.157, 53.394, 49.139 and 45.597 %, respectively. The corresponding values for cumulative amount of drug permeated for the said formulation were 43.013, 40.429, 37.793, 41.522, 37.450 and 34.656 %, respectively. On the basis of in vitro drug release and skin permeation performance, formulation HP-1 was found to be better than other formulations and it was selected as the optimized formulation.